2011
DOI: 10.1017/jmech.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Propagation of a Reaction Front in Fixed Bed Combustion of Wood Particles

Abstract: The goal of the combustion research is to achieve optimum combustion mode. Reaction Front velocity is one of the most important parameter that is studied in this field. Most biomass consumed at the present time is burned in fixed or moving beds. Fixed-bed combustion systems are characterized by the slow combustion of large particles subjected to an oxidizing ambient. In this paper a model for propagation of a reaction front of wood particles in a fixed Bed is presented. Once the bed is ignited, an apparent fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the os moisture content has no effect on the maximum temperature. Although the effect of the moisture content has been sufficiently verified [24,29,42], the results warn against the generalization of such an effect on low moisture content fuels. Along the same line, several studies [43,44] have found that an increase in the moisture content decreases the ignition front propagation speed due to the energy that is consumed by the evaporation process, although no drastic changes in the reached temperature were observed up to a moisture content of greater than 20%.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the os moisture content has no effect on the maximum temperature. Although the effect of the moisture content has been sufficiently verified [24,29,42], the results warn against the generalization of such an effect on low moisture content fuels. Along the same line, several studies [43,44] have found that an increase in the moisture content decreases the ignition front propagation speed due to the energy that is consumed by the evaporation process, although no drastic changes in the reached temperature were observed up to a moisture content of greater than 20%.…”
Section: Resultsmentioning
confidence: 92%
“…The highest calorific value of the fuel determines the ignition front speed (the ignition mass flow) [12]. However, high bed temperatures could lead to ash fusion, which, in turn, reduces the energy that is released in the bed [29].…”
Section: Variable Selectionmentioning
confidence: 99%
“…The fixed-bed combustion process is influenced by characteristic fuel-dependent parameters. The most important are as follows [11,[27][28][29]:…”
Section: Apmentioning
confidence: 99%
“…Thus, most papers published on this issue are based on statistical techniques such as multivariate data analysis [10] or mathematical models of dependence [11][12][13]. These multi-criteria decision analysis methods are used as tools for the classification and selection of the best alternative amongst a set of options.…”
Section: Introductionmentioning
confidence: 99%